The Ins and Outs of Icelandic Unemployment - Einarsson, Bjarni G. (Tímarit um viðskipti og efnahagsmál, 2016)
This paper presents new data on Icelandic labour market flows between employment, unemployment, and inactivity, constructed from the microdata in Statistics Iceland‘s Labour Force Survey (LFS). An analysis of the contribution of the transition rates to the dynamics of unemployment is then performed. Assuming a fixed labour force yields results comparable to previous estimates in Iceland, with a third of the variation in steady-state unemployment explained by the job finding rate, a significant departure from what is found in Anglo-Saxon, continental European, and Nordic economies. Taking account of movements in and out of the labour force has a significant effect on contributions of transition rates to variations in steady-state unemployment, with inactivity transitions accounting for roughly a third of the variability in steady-state unemployment and a dead-even split of the remaining two-thirds between the employment-unemployment and unemployment-employment transition rates. This contribution of inactivity transitions is comparable to that in the UK, US, and Spain. The background information available in the LFS indicates that some heterogeneity exists in the contributions by gender. The participation margin is thus an important source of variation in unemployment and needs to be accounted for to fully understand the drivers of Icelandic labour market fluctuations. Furthermore, ignoring transitions in and out of the labour force generates misleading results on the relative importance of the transition rates between employment and unemployment states in Iceland.